TINJAUAN EKONOMI ISLAM TERHADAP PELAYANAN MANASIK, PROMOSI DAN GAYA KEPEMIMPINAN PADA TRAVEL UMRAH DI KABUPATEN TASIKMALAYA - Nurbaeti Affandie; Hasan Basri; Nailul Mubarok (ARMUZNA : Jurnal Manajemen Haji dan Umrah (MHU), 2024)
This research is motivated by the large number of discussions from outside about the current management of KBIHU with the large number of sharia banks being established and the current very tight competition. So the author has an interest in how services, promotions exist at KBIHU, what practices and leadership styles are provided by a leader to employees. To be able to provide good service and promotions that are in accordance with Islamic Economics. The purpose of this research is to find out the services, promotions that occur at KBIHU and whether or not they are appropriate in reviewing Islamic economics. To obtain this research, the author used data collection techniques in the form of interviews, observation and documentation. This research approach uses a qualitative approach with a case study research method. For data analysis, data reduction, presentation and conclusions are used. The results of this research show that the service that occurs in transactions between employees and customers is able to provide good service in accordance with Islamic views. In practice at KBIHU there are Islamic values. The promotions given really create purity in banking and customers really believe that KBIHU is free from haram things and is pure in accordance with Islamic rules. As well as his leadership style which is carried out in terms of putting the subordinates he leads first, carrying out good mandates and not only in management, bank management or its concepts. However, here the leaders create KBIHU members who can behave well in accordance withIslamic values ​​and prioritize the priority of worship. So that many KBIHU employees become better at worship because of the habit of doing it frequently.